Supressividade a Fusarium oxysporum f. sp. cubense por produtos orgânicos - Heck, Daniel Winter [UNESP] (2015)
The induction of suppressiveness to Fusarium wilt in banana by the incorporation of Eucalyptus sawdust biochar (BC), shrimp shells (CC), composted sewage sludge (LE), clamshell (CM), bio-oil of rice husk (BA) and bio-oil of Eucalyptus sawdust (BE), fish emulsion (EP) and fish hydrolyzate (HP) to soil was evaluated. Soil chemical characteristics; the area under the curve of progress of the disease index (AUPCDI), final severity and internal discoloration of the rhizome; microbial respiration through the release of CO2; the populations of F. oxysporum, fungi and total bacteria; and inhibition of mycelial growth and microconidia germination through the compounds volatile toxic and aqueous extracts were the parameters evaluated. The CC and LE reduced final severity (50 and 37%, respectively) and the internal discoloration of the rhizome (56 and 36%, respectively). The incorporation of CC and CM reduced plant development in the early stages of cultivation, showing symptoms of phytotoxicity. The increase in pH, electric ...